The performance of lightweight concrete brick containing expanded polystyrene and palm oil fuel ash - Mohd Yassin, Nurain Izzati (2021)
The development of lightweight building materials has contributed to the construction industry, probably because of its advantages in terms of lower weight and low construction cost. One of the most demanded lightweight building material is lightweight concrete brick. Owing to rapid population growth, the Malaysian government is paying close attention to housing development, particularly in urban areas which consequently increase the bricks demand. Apart from the strong demand for bricks, the government is also concerned about the development of sustainable building materials. One of the most preferable lightweight material used in the production of lightweight concrete brick is Expanded Polystyrene (EPS). However concrete materials containing EPS were observed to be low in strength and fire resistance performance. On the other hand, Palm Oil Fuel Ash (POFA) which is unprofitable agricultural waste that is extensively generated by the palm oil mill has been categorised as one of the pozzolanic materials that could be used as a cement replacement. Additionally, it is found that the optimum amount of POFA replacement could enhance the strength and also fire resistance performance of a concrete materials. Therefore, in the present study a new combination of replacement materials which is EPS and POFA as sand and cement replacement in the production of lightweight concrete brick is proposed. In this study there are 30 different types of concrete bricks made up of 0%, 20%, 30%, 40%, 50% of EPS replacement and 0%, 5%, 10%, 15%, 20% 25% of POFA replacement. The parameters measured for each types of brick include hardened brick density, compressive strength, water absorption, initial rate of absorption and fire resistance. On the basis of the findings, it is found that this new development of brick has certain advantages that are lighter in mass, high in strength and good fire protection in addition to being environmentally friendly. To summarise, brick sample consist of 40% of EPS and 20% of POFA (E40P20) has been classified as the optimum brick design.